1986
DOI: 10.1007/bf00027136
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the Mu1 transposable element into the first intron of maize Adh1 interferes with transcript elongation but does not disrupt chromatin structure

Abstract: The presence of the Mu1 transposable element within the first intervening sequence of the maize Adh1 gene interfered with transcription through that gene. Insertion of the element did not have an apparent effect on transcription initiation or chromatin structure. In nuclei isolated from anaerobically induced roots, in which Adh1 is transcriptionally active, a subset of the Adh1 chromatin is arranged in a unique conformation characterized by a generalized sensitivity to nucleases, specific DNAase I sensitive si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…This conclusion is consistent with two previous reports. Nuclear run-off assays were used to analyze the Adhl-S3034 allele (Vayda and Freeling, 1986), and it was found that the Adhl-S transcript RNA did not effectively traverse the M u l element, suggesting that it was polyadenylated or terminated. Sequence analysis of seven cDNA clones (Ortiz and Strommer, 1990) derived from the Adhl-S3034 and Adh 1 -S4477 alleles under hypoxic stress demonstrated that polyadenylation was occurring within the AT-rich central region of Mul as well as in the TIR sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is consistent with two previous reports. Nuclear run-off assays were used to analyze the Adhl-S3034 allele (Vayda and Freeling, 1986), and it was found that the Adhl-S transcript RNA did not effectively traverse the M u l element, suggesting that it was polyadenylated or terminated. Sequence analysis of seven cDNA clones (Ortiz and Strommer, 1990) derived from the Adhl-S3034 and Adh 1 -S4477 alleles under hypoxic stress demonstrated that polyadenylation was occurring within the AT-rich central region of Mul as well as in the TIR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Rowland and Strommer (1 985), using nuclear run-off assays, suggested that the Mul element affected transcription initiation but not RNA processing. In contrast, Vayda and Freeling (1986) concluded from their nuclear run-off assays that transcription initiation was unaffected but that transcription elongation was impeded in some way by the Mul sequences. In a recent study, Ortiz and Strommer (1990) concluded that RNA processing of the Mul -containing chimeric transcripts was altered by aberrant splicing and by cryptic polyadenylation during hypoxic stress; these conclusions were based on RNA gel blots and the sequences of severa1 cDNAs of Adhl-S3034 transcripts from hypoxic roots.…”
Section: Introductionmentioning
confidence: 97%
“…SC) and alcohol dehydrogenase (Fig. SD) are associated with anaerobic metabolism in other plant species (10,14,26,30), and the protein products of these genes are detected by Western blot analysis (19) in tubers incubated under hypoxic conditions for 24 h (Fig. 5, E and F) prevents the accumulation of the wound-inducible class of RNA species.…”
Section: Markers Of the Aerobic Wound Responsementioning
confidence: 94%
“…RNA species were identified by formaldehyde agarose gel electrophoresis and Northern blot analyses using the methods described previously (20). In all analyses, equal amounts (30 …”
Section: Rna Analysesmentioning
confidence: 99%
“…The absence of other homologies of substantial length (>10 base pairs) between the promoters ofthese two genes supports the suggestion that the conserved sequences may have a functional role. The ARE also corresponds to one of the nuclease-sensitive regions of Adhi in the chromatin of nuclei isolated from anaerobic roots (5,21). Increased nuclease sensitivity is often associated with genes in a transcriptionally active state (22) and would suggest that the ARE may be part ofa transcriptionally active region in the chromatin of anaerobic maize roots.…”
mentioning
confidence: 99%